Tourism Human Resource Competency Development in Supporting Digital Destination Branding in Serang Regency - Abdul Muhit; Siti Sofiyah; Yeti Asmawati; Yanto Heryanto; Dian Evariana; Nora Asriani (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyse the development of tourism human resource competencies in supporting digital destination branding in Serang Regency and to identify factors that influence the effectiveness of digital tourism promotion. Methodology: The study used a qualitative case study approach. Data were collected through interviews, observations, and documentation related to digital tourism promotion. Analysis followed data reduction, data display, and conclusion verification procedures. Results: The study found that Serang Regency possesses significant tourism potential supported by natural, cultural, and religious attractions. However, the effectiveness of digital promotion remains influenced by varying levels of tourism human resource competencies, particularly in digital communication and social media management. Findings: Tourism stakeholders have begun utilising digital platforms for destination promotion, although the level of digital literacy and strategic branding capability remains uneven. Novelty: This study highlights the strategic role of tourism human capital development in strengthening digital destination branding at the regional level. Originality: The research provides a contextual analysis of tourism human resource competency development in supporting digital tourism promotion in Serang Regency. Conclusion: Strengthening tourism human resource competencies through training and collaborative programs is essential for improving digital destination branding and enhancing tourism competitiveness. Type of Paper: Research article.